Coaches and parents hold contrasting perceptions of optimal youth development activities in track and field athletics - Kearney, P. E.; Comyns, T. M.; Hayes, P. R. (International Journal of Sports Science & Coaching, 2020)
This study examined track and field coaches` and parents` knowledge of (a) the relationship between adolescent and later success, (b) factors contributing to adolescent success, particularly in relation to relative age effects, and (c) optimal athlete development practices, such as the timing of sport specialisation. Fifty-two coaches and 116 parents completed a survey comprising both closed and open questions. Compared to coaches, parents were more likely to believe that successful adults had achieved success during early adolescence and to connect that success to innate ability rather than relative development. However, there was no difference in the proportion of parents and coaches who reported familiarity with the relative age effect (approximately 50%). The most pronounced differences between coaches and players were in relation to optimal youth development practices, with parents more likely to encourage year-round training at an earlier age, and specialising in a single sport at an earlier age. Contrasting the knowledge reported by coaches and parents with the results of quantitative studies of youth development suggests that bespoke education is required for both groups. Furthermore, the explanations provided by parents and coaches for their beliefs about youth sport practices suggest that professional bodies need to provide more nuanced instruction to stakeholders on how to implement general guidelines on healthy youth sport practices into their individual practice.